NUMERICAL SIMULATION OF THE MOVEMENT OF SMOOTH PARTICLES AT THE ELECTROMAGNETIC SEPARATORS WITH DRUM - TUDOR CĂSĂNDROIU; GABRIELA VALERIA CIOBANU; LIANA ALEXANDRA VIŞAN (Journal of Engineering Studies and Research)
The paper presents the main theoretical elements underlying the seeds separation process after their surface. During the seed cleaning and sorting process according to the surface condition machines with electromagnetic or magnetic separators drums are used. In this paper is made a comparative theoretical analyze of smooth seeds movement on electromagnetic drum surface and trajectory in free flight, neglecting and taking into consideration air resistance, detached from the separation drum and it is evaluated the collection area of detached seeds. On this basis, were carried out several case studies and numerical simulations for three different machines.